The elevating power of literature - Spohr, Louise Mary (My University, 1899)
Introduction: Literature is the expression of ideals. It is the crystallization of thought. It is the character of a nation written in its books; its emotions throbbing in its drama, songs and ballads. It its true sense, literature deals with the emotions of the human soul. Its true study is not a study of words, of grammatical constructions or of rhetorical figures. It is nothing less than a study of life, itself, of whatever is best and highest in life expressed in the best and highest way. Every work of art, be it a cathedral, a statue, a painting or a poem, is the expression of some idea in the mind of the artist, the worth of which is determined by its manifestations of truth and beauty.
Citation: Spohr, Louise Mary. The elevating power of literature. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Ancient Literature; Modern Literature; Theses; Manuscripts (documents)